Assessment of the Need for Dental Treatment Resulting From Dental Trauma in 12-Year-Old Brazilian Schoolchildren: A Cross-Sectional Study - Haroldo Neves de Paiva; Cibelly Mara Pereira Araújo; Kayke Braulio Silva; Talita Torquato Vinhal Silva; Paulo Messias de Oliveira Filho; Paula Cristina Pelli Paiva (Association of Support to Oral Health Research (APESB), 2022)
Objective: To identify the need for restorative treatment in 12-year-old Brazilian schoolchildren with dental trauma and its association with clinical and socioeconomic factors. Material and Methods: A cross- sectional population-based study was carried out with sample composed of 588 12-year-old students from the city of Diamantina, Minas Gerais, Brazil. Data were collected from August to November 2016 through clinical examination, adopting the Andreasen classification and semi-structured questionnaire to verify the etiology and location of the accident that resulted in dental trauma. Statistical analysis included the frequency distribution and bi and multivariate analysis, with 5% significance level. Results: The presence of 219 traumatized teeth in 176 students was observed (29.9%). The main lesion was enamel fracture (41.4%), followed by enamel and dentin fracture (39.4%). The presence of restorative treatment was observed only in 11.5% of students. Fall (43.5%) was the most frequent etiology, followed by accidents on the streets (35.8%). Need for treatment was present in 53.4% of adolescents. Statistically significant association between males (p=0.010), severe overjet (p<0.0001) and inadequate lip protection (p<0.0001) and  presence of dental trauma was observed. Maternal schooling over 8 years of study was statistically associated with need for restorative treatment (OR = 2.047; CI: 1.099-3.813; p=0.023). Conclusion: Prevalence of dental trauma, need for restorative treatment and number of adolescents with no access to restorative treatment in this study were high, point out that the health system is unable to satisfactorily prevent dental trauma and absorb all dental treatment demand resulting from dental trauma.